Horizontal Coffee Roaster Design with Temperature and Time Control - I Ketut Suherman; I Wayan Suwirya; Ni Wayan Merda Surya Dewi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
National coffee have bean production reaches 600,000 tons for a year, only 20% that can be processed and marketed in to secondary products by roasted coffee, ground coffee, fast food coffee, and several types of secondary products derived from its derivatives and processing. The factors need to be considered when roasting, including temperature, time, expertise, and roasting techniques with a tool that is designed has dimension length 50 cm width 45 cm and height 110 cm. Coffee beans are roasted using a teflon griddle without a 25 cm cover diameter and Teflon griddle with a 16 cm cover diameter. The treatments studied were temperatures around 180 to 215oC with 12 minutes roasting time. The temperature treatment and roasting time affect the changes in mechanical physical properties of the coffee, namely a faster decrease in water content, increased fragility and accelerate changes in the color of darkness. Roaster machine based on microcontroller using gas fuel is made only 3 settings of coffee profile results, namely light, medium and dark with a light time of 12.8 minutes, medium 17 minutes and dark 25 minutes with a temperature setting of 245 degrees Celsius. The price of